IMPLEMENTASI KOMUNIKASI EFEKTIF DALAM ORGANISASI PENDIDIKAN ISLAM: ANALISIS PSIKOLOGI ORGANISASI TERHADAP HUBUNGAN GURU DAN PIMPINAN DI MADRASAH TSANAWIYAH KIFAYATUL AKHYAR BANDUNG: IMPLEMENTASI KOMUNIKASI EFEKTIF DALAM ORGANISASI PENDIDIKAN ISLAM: ANALISIS PSIKOLOGI ORGANISASI TERHADAP HUBUNGAN GURU DAN PIMPINAN DI MADRASAH TSANAWIYAH KIFAYATUL AKHYAR BANDUNG - l luqman; Mulyawan Safwandy Nugraha (Institut Agama Islam Sahid (INAIS) Bogor, 2026)
This qualitative case study analyzes the implementation of effective communication between teachers and leaders at MTs Kifayatul Akhyar Bandung through the lens of organizational psychology. The study reveals that communication effectiveness depends not only on technical aspects, but primarily on the synergy between psychological principles and internalized Islamic values within the organizational culture. The findings indicate that communication which fulfills teachers' psychological needs through the application of organizational justice, the provision of psychological safety in syura (consultation) forums, and the delivery of developmental feedback with courtesy (adab al-nasihah) organically integrates with Islamic communication ethics such as shiddiq (truthfulness) and rahmah (compassion). This synergy is mediated by a leadership style that combines transformational, servant, and spiritual aspects, thereby giving rise to an adaptive, multidirectional communication pattern. This pattern ultimately creates a healthy organizational climate, characterized by high levels of trust, social cohesion, and openness, which serves as a solid foundation for managing conflict constructively and implementing change participatively. The study concludes that a holistic communication model integrating functional effectiveness, psychological well-being, and spiritual significance is key to the success of Islamic educational organizations in achieving academic goals and building a productive work environment imbued with blessing (barakah).